Improve Marketing Performance through Market Orientation Entrepreneurship and Strategi Performance at SME’s Oyster Mushroom in Temanggung Regency - Alimah, Sri; Murwatinigsih, Murwatinigsih (Management Analysis Journal, 2019)
The purpose of this research to analyze market orientations sphere creativity strategy influential on the performance marketing of the general perpetrator's oysters fungus in Temanggung. As for the respondent perpetrators oyster fungus in Temanggung sample as much as 100 respondent. While to analyze the technic analyze structural equation modeling. The Result of the performance marketing, influential of the creativity strategi, Sphere influential oh the market orientation, Sphere influential in the performance marketing, Market orientation influential of the creativity strategy.